Photobiomodulation of Cytochrome c Oxidase by Chronic Transcranial Laser in Young and Aged Brains - Cardoso, Fabrízio dos Santos; Barrett, Douglas W.; Wade, Zachary; Gomes da Silva, Sérgio; Gonzalez-Lima, F. (Frontiers in Neuroscience, 2022)
In cellular bioenergetics, cytochrome c oxidase (CCO) is the enzyme responsible for oxygen consumption in the mitochondrial electron transport chain, which drives oxidative phosphorylation for adenosine triphosphate (ATP) production. CCO is also the major intracellular acceptor of photons in the light wavelengths used for photobiomodulation (PBM). Brain function is critically dependent on oxygen consumption by CCO for ATP production. Therefore, our objectives were (1) to conduct the first detailed brain mapping study of the effects of PBM on regional CCO activity, and (2) to compare the chronic effects of PBM on young and aged brains. Specifically, we used quantitative CCO histochemistry to map the differences in CCO activity of brain regions in healthy young (4 months old) and aged (20 months old) rats from control groups with sham stimulation and from treated groups with 58 consecutive days of transcranial laser PBM (810 nm wavelength and 100 mW power). We found that aging predominantly decreased regional brain CCO activity and systems-level functional connectivity, while the chronic laser stimulation predominantly reversed these age-related effects. We concluded that chronic PBM modified the effects of aging by causing the CCO activity on brain regions in laser-treated aged rats to reach levels similar to those found in young rats. Given the crucial role of CCO in bioenergetics, PBM may be used to augment brain and behavioral functions of older individuals by improving oxidative energy metabolism.